Taxonomic turmoil around the genus Anoplistes Audinet-Serville, 1833 (Coleoptera: Cerambycidae) in the Uvs Nuur Basin: a new species, a new synonym, and a species reinstatement - Karpiński, Lech (Zootaxa, 2026)
Anoplistes minutus Hammarström, 1892 stat. rev., previously regarded as a subspecies of A. halodendri (Pallas, 1773), is reinstated as a valid species based on its clear morphological difference from the latter. This taxonomic decision automatically implies that all specimens of A. halodendri from Mongolia, incorrectly assigned to A. halodendri minutus sensu Danilevsky and Smetana (2010), should be referred to the nominotypical subspecies. Subsequently, A. tuvensis syn. nov. is considered as a junior synonym of A. minutus stat. rev.: Anoplistes minutus Hammarström, 1892 = Anoplistes tuvensis (Tsherepanov, 1978). Finally, Anoplistes pseudotuvensis sp. nov. from northwestern Mongolia is described based on a series of six specimens collected in 1963 and a detailed morphological analysis using scanning electron microscopy. This overlooked taxon was previously confused and misidentified with A. tuvensis syn. nov., owing to their similar distribution areas, or misidentified with A. mongolicus Ganglbauer, 1889. The new species can be easily distinguished morphologically from A. minutus stat. rev. (= A. tuvensis syn. nov.) as they belong to different species groups. The two taxa also differ ecologically, being associated with different host plants and occurring in distinct habitats, as presented in this paper. Habitus of all the above-mentioned taxa is illustrated with high-resolution stacked images. The description of this new species and the reassessment of the two remaining taxa contribute to resolving the complex taxonomy of the genus and provides a basis for future revision integrating morphological, ecological, and molecular data.